Tinjauan Yuridis Keterlibatan Anak Dalam Perdagangan Narkotika di Indonesia - Santoso, Dwi Rahmadi; Levina Yustitianingtyas (Faculty of Law, University of Muhammadiyaha Surabaya, 2025)
Drug trafficking is a serious crime that not only threatens social order and public health, but is also increasingly worrying with the increasing involvement of children in its networks. This phenomenon creates a complex dilemma where children are often exploited and become victims of syndicates, but in practice are actually treated as perpetrators, so that an in-depth legal study of regulations, forms of legal sanctions, protection, and obstacles to handling children in the drug trade is crucial to ensure justice that sides with children. This study aims to analyze the forms of legal sanctions and protection for children involved in the drug trade based on Law Number 35 of 2009, Law Number 11 of 2012, the Criminal Code, and Law Number 35 of 2014. This study uses a normative research method through a legislative approach. The results of this study indicate that legal sanctions for children involved in drug trafficking in Indonesia, although strictly regulated in Law Number 35 of 2009 concerning Narcotics, must be aligned with the principles of child protection in Law Number 11 of 2012 concerning the Juvenile Criminal Justice System (SPPA), Law Number 35 of 2014 concerning Child Protection, and the Criminal Code (KUHP). This treatment includes limiting the duration of the sentence, granting special rights to assistance, and rehabilitation so that children can return to their social environment in a positive manner and avoid the negative impacts of the criminal justice system. It is concluded that optimal protection and reintegration of children in this case requires multi-stakeholder synergy, starting from the consistency of law enforcement in implementing diversion and restorative justice, to strengthening the role of families and communities supported by comprehensive government policies. This research is presented as a general review.